(3efgL JYdje GddZI GdYQHjI hBOGHgG aj GdUaha GdeJhSWI aj dHfGf(B:(3GdhGbY hGdeQJLis - (3MjOhQI, Ydj YHOGddgs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2003)
(3JfGhdJ gPg GdCWQhMI efgL JYdje GddZI GdYQHjI hBOGHgG aj GdUaha GdeJhSWI aj dHfGf(B. (3acGfJ YHGQI Yf YQV daUhd JJfGhd eMGhQ YOI dgG YdGbI HGddZI GdYQHjI, aGdGfWdGbI cGfJ ef JYQja CgejI GddZI GdYQHjI hBOGHgG ddeQMdI GdeJhSWI hCgejJgG hCfhGYgG, MSH Gdeaghe GdMOjK, EVGaI Edi GdYhGed GdeDKQI hGdJhLgGJ GdMOjKI eY JaUjd TGed daQhYgG(B. (3aj GdeMhQ GdKGfj YQVJ GdYfGUQ GdJQHhjI ddefgL hGdZGjGJ hGdCgOGa efg hJdGgG aj GdeMhQ GdKGdK JMdjd GdefgL hJHjGf NUGFUg GdYGeI GdJj jJeJY HgG hJCKjQgG Ydi JdejP GdeQMdI GdeJhSWI ddhUhd Edi GdYfGUQ GdSdHjI hGdEjLGHjI OGNdg(B. (3HGdEVGaI Edi eMGhQ CNQi JJfGhd eG LGA aj GdgjcdjI GdLOjOI hZGjGJgG hCgOGagG, ceG WQMJ WQGFb JOQjS GddZI GdYQHjI hCOGHgG aj GdeQMdI GdeJhSWI hYdGbI GdefgL GdLOjO aj gPg GdNWhGJ(B. (3cPdc HjfJ GdOQGSI GdCSS hGdefWdbGJ GdCSGSjI dHfGA GdefgL GdLOjO ddZI GdYQHjI hBOGHgG, eVjaI OhQ GdeWGdYI hGdecJHI GdeOQSjI hGdJQLeI aj JWqhQg(B. (3haj fgGjI GdCWQhMI TZd GdaUd GdCNjQ ecGfkG dJbjje GddZI GdYQHjI hBOGHgG HTcd YGe hCHQR GdKZQGJ GdJj XgQJ ef NdGd GdEeJMGfGJ GdQSejI eY JbOje GbJQGMGJ dehGLgJgG hJWhjQgG(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Cycle moyen L$1 (Benseignement de la langue Arabe Curriculums; Educational prospective; Intermediate Education Arabic Language education Curricula; Prospective; (3GdGSJTQGas; (3GdeQMdI GdeJhSWI JYdje GddZI GdYQHjI GdefGgLs